2012
DOI: 10.1186/1475-2891-11-97
|View full text |Cite
|
Sign up to set email alerts
|

In depth analysis of risk factors for coeliac disease amongst children under 18 years Old in the Gaza strip. A cross sectional study

Abstract: Coeliac disease is an important clinical disorder affecting the human gastrointestinal tract leading to multiple signs and symptoms in different body organs. This disease was the subject of a cross sectional descriptive-analytic study conducted in the Gaza Strip during 2010. Objectives were oriented to identify and verify several variables and attributes affecting the prognosis of coeliac disease in the patients. Ninety five children out of 113 patients were arranged into two groups according to age from 2 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…The incidence of CD in Punjabis (Sikhs, Hindus, and Muslims) is eight times greater than in Gujaratis (Hindus and Muslims) and four times higher than in Leicester, England ( 22 ). Data in the Arabic population, especially in Bedouins, is limited, with a prevalence of 0.02% in the Gaza strip ( 14 ) and incidence of 1:2800 live births in Jordanian children ( 13 ). Additionally, in Sweden there was a decreased incidence of CD in second-generation immigrants and some groups of foreign adoptees, which supports the claim that ethnic genetic heterogeneity may contribute to the variation in CD incidence ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of CD in Punjabis (Sikhs, Hindus, and Muslims) is eight times greater than in Gujaratis (Hindus and Muslims) and four times higher than in Leicester, England ( 22 ). Data in the Arabic population, especially in Bedouins, is limited, with a prevalence of 0.02% in the Gaza strip ( 14 ) and incidence of 1:2800 live births in Jordanian children ( 13 ). Additionally, in Sweden there was a decreased incidence of CD in second-generation immigrants and some groups of foreign adoptees, which supports the claim that ethnic genetic heterogeneity may contribute to the variation in CD incidence ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Assa et al reported that the prevalence of CD in Israel was significantly lower in subjects from lower socioeconomic status backgrounds, as well as those of African, Asian and former Soviet Union origin ( 12 ). The presence of CD in Arab children has been the subject of only a few reports and were based only on small case base series ( 13 , 14 ). The Bedouins in Israel are a subgroup within the minority Arab population, have unique historical, social and cultural characteristics, and an extremely high rate of consanguineous marriage ( 5 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…These results, altogether, showed an unbalanced diet in terms of micronutrients, that were in accordance with those shown in several studies. 14,[61][62][63] On the other hand, almost all the study participants from both genders showed a high daily consumption of iron. This finding contradicts the results reported in other studies.…”
Section: Dietary Supplements Use and Typementioning
confidence: 95%
“…Most studies used convenience (n = 20), purposive (n = 5), and volunteer (n = 11) sampling strategies, and recruited from specialist pediatric gastroenterology clinics or coeliac organizations, which risks selection bias and lower representativeness of the wider target population. Five studies did not report the recruitment methods used (14)(15)(16)(17)(18).…”
Section: Summary Of Study Qualitymentioning
confidence: 99%
“…Three studies (16,33,34) were questionnaire validation studies. All quantitative studies used appropriate statistical tests, except 1 which did not describe the data analysis strategy used (14). Qualitative studies used grounded theory (32,35), interpretative phenomenology (31), thematic analysis (5), or were appropriately guided by previous frameworks (15,36).…”
Section: Summary Of Study Qualitymentioning
confidence: 99%